If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(y + 6) = 13 Reorder the terms: 3(6 + y) = 13 (6 * 3 + y * 3) = 13 (18 + 3y) = 13 Solving 18 + 3y = 13 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 3y = 13 + -18 Combine like terms: 18 + -18 = 0 0 + 3y = 13 + -18 3y = 13 + -18 Combine like terms: 13 + -18 = -5 3y = -5 Divide each side by '3'. y = -1.666666667 Simplifying y = -1.666666667
| 6+4x=-58 | | (a+b)+2a=180 | | 1+8+x=23 | | 8.3=4k-2.4 | | x^4-4x^3+4x^2-16x=0 | | Y=8x+4.9 | | -6(3x+8)=-18x-48 | | x^4-4x^3+4x^2=16x | | 4(-2x+5)= | | 175-4p=375 | | 0=w^2-3w-1890 | | Y=10sin | | 4x+6=2x-30 | | 4k+2(5k-6)=-3-39 | | 6x-54=-24x | | 3(x-2)=5(x+8) | | 24-3k=-2k | | 6-6=8x+4x | | x^2-4xy+y^2-16=0 | | 0.15(40)+.60X=0.40(40+X) | | 65+5=40 | | 3x-7/4=4x+5/3 | | 3x-4+2x=5x-6 | | 16-(3m+3)=4+4m-19 | | 42=4y-10 | | p(x)=0.1(x-3)(x-150) | | -56=20-(-f) | | 1x-4=13+43 | | 32=30-16 | | 78-x=21 | | N^2-1=8 | | 6x+5=40 |